Supplementation of Yupingfeng polysaccharides in low fishmeal diets enhances intestinal health through influencing the intestinal barrier, immunity, and microflora in Macrobrachium rosenbergii - Liu, Mingyang; Sun, Cunxin; Zhou, Qunlan; Xu, Pao; Wang, Aimin; Zheng, Xiaochuan; Liu, Bo (Frontiers in Immunology, 2024)
IntroductionThis study aimed to investigate the effects of a low-fishmeal diet (LF, substituting soybean meal for 40% fish meal) and the supplementation of 500 mg/kg and 1000 mg/kg Yu Ping Feng (YPF) polysaccharides on the growth performance, antioxidant enzyme activities, intestinal ultrastructure, non-specific immunity, and microbiota of Macrobrachium rosenbergii.MethodsThe study involved the administration of different diets to M. rosenbergii, including a control diet, a low-fishmeal diet (LF), and LF diets supplemented with 500 mg/kg and 1000 mg/kg YPF polysaccharides. Growth performance, antioxidant enzyme activities, intestinal ultrastructure, non-specific immunity, and microbiota were assessed.ResultsThe LF diet significantly reduced growth performance parameters compared to the control group. However, YPF supplementation notably improved these parameters, with the greatest improvement observed at a 1000 mg/kg dosage. Antioxidant enzyme activities (SOD, GSH-PX) were diminished in the LF group, accompanied by elevated MDA levels, whereas YPF supplementation restored these activities and reduced MDA levels. Ultrastructural analysis revealed that the LF diet caused intestinal villi detachment and peritrophic matrix (PM) shedding, which were alleviated by YPF. Gene expression related to PM formation (GS, CHS, EcPT) was downregulated in the LF group but significantly upregulated in the 1000P group. Non-specific immune gene expressions (IMD, Relish, IκBα) and enzyme activities (NO, iNOS) were suppressed in the LF group but enhanced by YPF supplementation. Microbial community analysis showed reduced diversity and altered composition in the LF group, with increased Proteobacteria and decreased Firmicutes, which were partially restored by YPF. Correlation analysis revealed that Lactobacillus and Chitinibacter play pivotal roles in regulating intestinal health. Lactobacillus exhibited a positive relationship with the intestinal PM and immune-related indicators, whereas Chitinibacter was negatively associated with these factors.DiscussionThese results highlight the adverse impacts of a low-fishmeal diet on the intestinal health of M. rosenbergii and demonstrate the beneficial effects of YPF polysaccharides in alleviating these negative consequences through various mechanisms, including improved growth performance, enhanced antioxidant enzyme activities, restored intestinal ultrastructure, and modulated immune responses. The findings suggest that YPF supplementation could be a valuable strategy for mitigating the negative effects of low-fishmeal diets in aaquaculture.